Influence of surface properties on electro-chemical supercapacitors utilizing Callerya atropurpurea pod derived porous nanocarbons: Structure property relationship between porous structures to energy storage devices - Bhat, Vinay S.; S., Supriya; Jayeoye, Titilope John; Rujiralai, Thitima; Sirimahachai, Uraiwan; Chong, Kwok Feng; Hegde, Gurumurthy (WILEY‐VCH, 2020)
Surface properties always play a dominant role in the energy storage devices. Understanding the surface phenomena is the key to tune the energy storage device using biowaste based porous nano carbons. Here, Callerya atropurpurea pod derived peculiar porous nano carbons are synthesized by pyrolysis at different temperatures without any synthetic templates approach. Elaborate analysis of surface textures on the effect of pore size, volume and specific surface area on specific capacitance and frequency response behavior of nano carbons were studied in detail. Electrochemical characterizations establish the mutuality of porosity and micro textural properties of nano carbons with specific capacitance. The electrochemical characterization of the novel materials as super capacitor electrode shows a high specific capacitance of 326.54 F g−1at 0.25 A g−1in 1.0 MKOH. A practical symmetric super capacitor device is fabricated with a specific capacitance of 86.38 F g−1at 0.1 A g−1, and high energy density of 27.0 Wh kg−1.This symmetric super capacitor also possesses outstanding capacitance retention of 92.16% for 5000 charge discharge cycles and also stability of 97.17%, after volt-age holding at the maximum voltage for 100 hours. Present manuscript gives the strong evidence for structure-property relationships so that one can tune the energy storage devices effectively